Peran Peran Pola Komunikasi Orang Tua dalam Pemerolehan Bahasa Pertama dan Kedua Anak Usia Dini: Studi Literatur - Nurlailah; Gita Wulandari; Putri Zahrani; Seftika Ramayanti; Lulu R. Farhanani; Siti Nurhidayah; Amanda Maharani (Universitas Darunnajah, 2026)
This study aims to examine the role of parental communication patterns in the process of first language (L1) and second language (L2) acquisition in early childhood through a literature review approach. Parental communication patterns, including responsiveness, frequency of verbal interaction, use of child-directed speech (CDS), and emotional engagement, have been shown to significantly influence children's linguistic development. This study analyzes various literature sources from 2016 to 2026 relevant to the topic of early childhood language acquisition. The findings indicate that rich, responsive, and consistent communication patterns positively contribute to the speed and breadth of both L1 and L2 acquisition. Furthermore, it was found that a structured bilingual environment with active parental communication support can optimize children's second language acquisition without impeding first language development. The implications of this study emphasize the importance of parental education regarding effective communication strategies in supporting the linguistic development of early childhood.